Development of an anisokinetic particle sampling probe for use in a gas turbine engine compressor - Olshefski, Kristopher; Collins, Addison; Coulon, Thomas; Lowe, Todd; Ng, Wing (Frontiers in Mechanical Engineering, 2022)
Sand and dust particle ingestion is an inevitability for aircraft operating in arid environments. For conventional takeoff and landing aircraft, significant dust can be ingested into the gas turbine powerplant. Helicopters and vertical takeoff and landing (VTOL) aircraft are at especially high risk due to their tendency to blow significant debris into the air during takeoff and landing operations. The present study highlights the development of an anisokinetic particle sampling probe for use in aircraft engines to obtain real-time measurement of ingested particles often present in these harsh environments. Offtake of particles during engine operation in dusty conditions will provide researchers with an improved understanding of particle breakage tendency and component erosion susceptibility. Three foundational studies were conducted to establish a baseline understanding of probe performance: an aerodynamic study, a particle tracking study, and a particle sampling study. These studies were performed using the Free Jet rig at the Advanced Propulsion and Power Laboratory at Virginia Tech. Particles as large as 1.3 mm were sampled at Mach numbers where M=(0.25,0.70) and yaw angles ranging from 0 to 45 degrees relative to freestream, conditions not previously investigated. Results indicate that the probe operates sub-isokinetically throughout the full range of test conditions and that probe aerodynamic capture efficiency is inversely proportional to both Mach number and yaw angle. However, this efficiency limitation does not notably influence the sampling probe's ability to capture the test dust of interest. While the presence of the probe in the flow does result in an airflow velocity reduction of up to 55%, due to their relatively large Stokes numbers the particles of interest only experience a decrease of roughly 5%. These results indicate that this probe is capable of providing researchers with valuable particle size and shape information through effective particle sampling at particle sizes (100 μm < d_p < 1300 μm) and speeds (M > 0.25) not previously investigated.